2016
DOI: 10.1530/erc-16-0328
|View full text |Cite
|
Sign up to set email alerts
|

WOMEN IN CANCER THEMATIC REVIEW: Thyroid-stimulating hormone in thyroid cancer: does it matter?

Abstract: Differentiated thyroid cancer is the most common endocrine malignancy and the incidence is increasing rapidly worldwide. Appropriate diagnosis and post-treatment monitoring of patients with thyroid tumours are critical. Fine needle aspiration cytology remains the gold standard for diagnosing thyroid cancer, and although there have been significant refinements to this technique, diagnostic surgery is often required for patients suspected to have malignancy. Serum thyroid-stimulating hormone (TSH) is higher in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 93 publications
1
29
0
Order By: Relevance
“…The main functions of TSH are regulation of thyroid hormones, facilitation of thyroid cell growth, excitation of the sodium iodide symporter, and adjustment of extrathyroidal effects. A study showed that long‐term high TSH levels leaded to hyperplasia and hypertrophy of the thyroid gland . A previous meta‐analysis of 28 studies suggested that an increased thyroid neoplasm risk was related to high TSH concentrations .…”
Section: Discussionmentioning
confidence: 99%
“…The main functions of TSH are regulation of thyroid hormones, facilitation of thyroid cell growth, excitation of the sodium iodide symporter, and adjustment of extrathyroidal effects. A study showed that long‐term high TSH levels leaded to hyperplasia and hypertrophy of the thyroid gland . A previous meta‐analysis of 28 studies suggested that an increased thyroid neoplasm risk was related to high TSH concentrations .…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Importantly, there is mounting evidence that exogenous subclinical thyrotoxicosis as a result of TSH suppression therapy may be detrimental with regard to long-term cardiovascular health by impairing cardiac contractility and arterial elasticity, [11][12][13] exacerbating angina and inducing atrial fibrillation (AF) in high-risk patients. 14 The aforementioned mechanism via which detrimental cardiovascular impact may be observed in patients with DTC was not demonstrated in a study involving 366 patients with thyroid cancer. 15 In contrast, a more recent observational study reported a three-fold increased risk of cardiovascular mortality in 414 patients with DTC compared to matched controls and suggested that this increase was associated with lower serum TSH concentrations.…”
mentioning
confidence: 92%
“…Importantly, there is mounting evidence that exogenous subclinical thyrotoxicosis as a result of TSH suppression therapy may be detrimental with regard to long‐term cardiovascular health by impairing cardiac contractility and arterial elasticity, exacerbating angina and inducing atrial fibrillation (AF) in high‐risk patients . Moreover, in preparation of adjuvant thyroid ablation therapy, when indicated, patients with DTC may also undergo a transient hypothyroid phase, in settings where recombinant human TSH is not used.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, chronic exposure to TSI has been associated with increased disease-specific mortality in thyroid cancer in some, but not all, studies (Belfiore et al 1990, Pellegriti et al 2013. Recently, multiple large cohort studies have found that increased levels of serum TSH are associated with increased subsequent risk of thyroid cancer (Nieto & Boelaert 2016). The largest study, recruiting 10,178 patients presenting with nodular thyroid disease for fine needle aspiration (FNA) biopsy, found an increasing odds ratio for papillary thyroid cancer (PTC) with incremental increases of TSH within the reference range of 0.4-3.4 IU/L (Fiore et al 2009).…”
Section: Tshr Stimulation and Thyroid Growthmentioning
confidence: 99%